Multicultural Education Based on Divinity and Unity Values to Improve Tolerance Character - Ramayani, Sri (Berpusi Publishing, 2024)
Multicultural education is one of the important approaches in shaping the character of Indonesia as a plural nation. This paper discusses the concept of multicultural education based on the values of divinity and unity, and how this approach can enhance the character of tolerance among students. Through literature review and descriptive analysis, the article emphasizes that the values of divinity and unity contained in Pancasila serve as the philosophical foundation of multicultural education in Indonesia. The research method employs a qualitative approach with library research and conceptual analysis. The findings indicate that multicultural education grounded in the values of divinity and unity can strengthen tolerance, solidarity, and respect for cultural, religious, and ethnic diversity. This article is expected to serve as a reference for educational practitioners in designing inclusive learning strategies oriented toward the development of tolerant character.